Economic diplomacy in action : the case of the Embassy of Portugal in the Czech Republic - Neiva, Ana Lúcia da Ponte (2016)
Economic diplomacy has become a key instrument of Governments' foreign policy and of the promotion of a country's interests abroad. The evolution of the economic content of diplomacy led to the intervention of new actors (e.g. international organizations, non-profit organizations). Despite the intervention of non-state actors, there is a strong consensus on the overall impact of economic diplomacy through the public-sector. As far as I could find out, there are no studies about the role of the Portuguese embassies. This work aims to analyse the role of the Portuguese embassy and the local delegation of AICEP in achieving the main goals of Portuguese economic diplomacy in the Czech Republic. A qualitative research strategy is adopted, applying the case study method to comprehend the role assumed by both organizations. Information collected during the 5 months of the internship and interviews of Portuguese firms with investments in the Czech Republic are main sources of information. The absence of a physical presence of the AICEP delegation in the Czech Republic led to the increasing role of the embassy at supporting Portuguese firms. The lack of human resources at the embassy and the geographic distance to AICEP’s delegation in Warsaw are considered to be major constraints regarding the promotion and support of bilateral trade and investment relations between the two countries. The achievement of economic diplomacy goals requires resources. After looking for a greater efficiency in the use of public resources (combining the resources of AICEP delegations with the embassies’ resources) it would make sense increase the cooperation with private actors, such as bilateral Chambers of Commerce and business associations.